2009
DOI: 10.4081/ijas.2009.s1.45
|View full text |Cite
|
Sign up to set email alerts
|

Main causes of poor welfare in intensively reared dairy cows

Abstract: The aim of this review is to summarise the main causes of poor welfare in intensively reared dairy cows. Intensive farming systems are considered, both from a structural and a managerial point of view, for their constraints that may limit animal welfare: possible physical activity; acceptable interactions with humans and other animals; feeding and watering, protection from climate, parasites, and diseases. The dairy farms managed according to the organic rules do not always guarantee, per se, better welfare co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 79 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Inadequate animal welfare conditions are known to cause chronic stress and numerous health issues in dairy farms (Abeni and Bertoni 2009), but objective and systematic assessment of animal welfare aspects, including comfort ability of facilities, is not routinely done by veterinarians and therefore, insufficient or poor cow comfort may be overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate animal welfare conditions are known to cause chronic stress and numerous health issues in dairy farms (Abeni and Bertoni 2009), but objective and systematic assessment of animal welfare aspects, including comfort ability of facilities, is not routinely done by veterinarians and therefore, insufficient or poor cow comfort may be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of animal welfare conditions provides an opportunity to address ethical issues and also to improve the productive performance of dairy farms (Abeni and Bertoni 2009), as cow discomfort is known to hinder full development of the productive potential. Various different studies have demonstrated that some facility-related aspects, as well as management practices, may influence animal health, longevity and reproductive and productive performance (Cook and Reinemann 2007;Erina et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Animal health contributes importantly to well‐being, and whenever an animal is diseased, its well‐being is compromised (Bertoni et al., ; Barkema et al., ). With regard to dairy cow welfare, the major topics include lameness, mastitis and metabolic disorders (Abeni and Bertoni, ; Barkema et al., ). A high metabolic load coming along with low plasma glucose concentrations and high plasma free fatty acids (FFA) and β ‐hydroxy‐butyric acid (BHBA) concentrations is an obvious risk factor for various diseases (Reist et al., ; Hachenberg et al., ; Graber et al., ) and compromised immune response (Zarrin et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…He reported an adverse effect on cows when the value of THI rises over 72. Heat stress in lactating dairy cows reduces DMI, rumen digestion (due to reduced blood flow in the digestive tract), rumen pH and secretion of saliva (Abeni, 2009). Hot weather conditions also modify cow behaviour.…”
Section: Introductionmentioning
confidence: 99%